A novel reverse two-hybrid method for the identification of missense mutations that disrupt protein–protein binding - Vincent, Olivier (Sci Rep, 2020)
The reverse two-hybrid system is a powerful method to select mutations that disrupt the interaction between two proteins and therefore to identify the residues involved in this interaction. However, the usefulness of this technique has been limited by its relative complexity when compared to the classical two-hybrid system, since an additional selection step is required to eliminate the high background of uninformative truncation mutants. We have developed a new method that combines the classical and reverse two-hybrid systems to select loss-of-binding missense mutations in a single step. The strategy used to select against truncation mutants is based on the two-hybrid interaction between a C-terminal fusion peptide and the Tsg101 protein. We have applied this method to identify mutations in human glucokinase (GK) that disrupt glucokinase regulatory protein (GKRP) binding. Our results indicate that this method is very efficient and eliminates all the truncation mutants and false positives. The mutated residues identified in GK are involved in the GKRP binding interface or in stabilizing the super-open conformation of GK that binds GKRP. This technique offers an improvement over existing methods in terms of speed, efficiency and simplicity and can be used to study any detectable protein interaction in the two-hybrid system.